Biochemical and microstructural assessment of minimally processed peaches subjected to high-pressure processing : implications on the freshness condition - Denoya, Gabriela Inés (2016)
Since the condition of freshness is closely linked to the definition of minimally processed fruits, it is generally assumed that they should be constituted by living tissues. High-pressure processing (HPP) has been proven to be successful in maintaining the freshness of foods, although the integrity of some tissues could be altered. The aim of this work was to assess different biochemical and microstructural changes experimented by the HPP-treated tissues. The following determinations were conducted in control and treated diced peaches: viability assay, microstructure analysis, relative expression of RNAm, and enzyme activities related to browning and anaerobic metabolism. Results showed that although HPP-treated tissues were not viable, changes in the expression of the RNAs of the enzymes evidenced that some metabolic processes were still active. In turn, the microstructure remained rather unaltered, while the enzymes tested were significantly inhibited. Then, although some characteristics of living tissues were modified in the HPP-treated fruits, they could be considered as fresh in appearance.